Os desafios e o papel das fundações de apoio: um estudo de caso da Fundação de Apoio Científico e Tecnológico do Tocantins - Passos Júnior, Edy César dos (Universidade Federal do Tocantins, 2016)
A subject bit unknown in Brazil and with few published works, on the support foundations for superior and technological education public institutions on Brazil. Such entity has been valuable for the development of science, technology and innovation. The present study searched to trace the legal nature of support foundations and their contribution to Brazilian Academy. For the deepening issue was held here a study case on the Scientific and Technological Support Foundation of Tocantins - FAPTO, the institution linked to Federal University of Tocantins - UFT. To analyze the importance of these foundations and the legal basis thereof, it carried out a detailed study on the legal status, internal organization, control systems and resource management, as well questionnaires and interviews with actors involved with FAPTO. The result of the research was the realization of financial and actuarial problems of the foundation, where a serie of budget deficit can lead this important entity to serious economic problems in the near future. Key Words: IFES; support foundation; science and technology; public/private partnership.